2008
DOI: 10.1007/s10549-008-0086-2
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of metastatic spread in triple-negative breast cancer

Abstract: The excess risk of distant recurrence in triple-negative breast cancers, versus other forms of cancer, is attributable in large part to an excess of visceral metastases in the first five years following diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
322
2
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 481 publications
(350 citation statements)
references
References 23 publications
19
322
2
7
Order By: Relevance
“…It had been reported that TNC patients had shorter survival after diagnosing brain metastasis when compared to non TNC counterparts and hence is a poor prognostic indicator (Saip et al, 2009). Consistent with findings reported in Western population (Rodriguez-Pinilla et al, 2006;Dent et al, 2009), we did not find any difference between the TNC and non TNC groups in incidence of bone metastasis.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It had been reported that TNC patients had shorter survival after diagnosing brain metastasis when compared to non TNC counterparts and hence is a poor prognostic indicator (Saip et al, 2009). Consistent with findings reported in Western population (Rodriguez-Pinilla et al, 2006;Dent et al, 2009), we did not find any difference between the TNC and non TNC groups in incidence of bone metastasis.…”
Section: Discussionsupporting
confidence: 90%
“…Majority of studies in the West showed worse prognosis for TNC group within 3-5 years (Tischkowitz et al, 2007;Dent et al, 2009), and some suggested the differences between TNC and non-TNC regarding overall survival wear off at 10 years of follow-up (Tischkowitz et al, 2007). In this aspect, we observed a similar breast cancer-specific mortality rate, disease-free survival and overall survival between groups.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Studies of the spread of breast cancer have shown that a longer interval free of pleural metastases is an indicator of a worse prognosis, (8,10,11) and this poor prognosis has been associated with factors such as the site of the metastasis and the identification of malignant cells in the pleural fluid (23) ; the expression of c-erbB-2 (21) ; the triple-negative phenotype (11,(15)(16)(17) ; and Ki-67 protein expression, which has been shown to be present in 63% of patients with malignant pleural effusion. (18,24,25) The worst breast cancer survival rates are in developing countries.…”
Section: Resultsmentioning
confidence: 99%
“…TNBC is associated with shortened disease-free interval post-surgery and post-adjuvant treatment and, ultimately, a shortened overall survival. [12][13][14][15] Furthermore, TNBCs are themselves a heterogeneous group within which the claudinlow subtype is associated with worst prognosis. 16 Compared to the overall prevalence of breast cancer, a limited number of reports have indicated exosomes and/or microvesicles to be of relevance in breast cancer.…”
Section: Introductionmentioning
confidence: 99%